The co-production of a ‘‘relevant’’ expertise – administrative and scientific cooperation in the French water policies elaboration and implementation - Deroubaix, J.F. (Hydrology and Earth System Sciences Discussions, 2007)
This paper aims at understanding the social and political uses of the principle of integrated management and its possible impacts on the elaboration and implementation processes of public policies in the French water management field. The academic and political innovations developed by scientists and agents of the administration these last 25 years are analysed, using some of the theoretical tools developed by the science studies and public policy analysis. We first focus on the construction of intellectual public policy communities such as the GIP Hydro systems, at the origin of large interdisciplinary research programs in the 1990s. A common cognitive framework is clearly built during this period on the good governance of the aquatic ecosystems and on the corresponding needs and practices of research. The second part of the paper focuses on the possibilities to build political communities and more or less integrated expertises in the decision making processes concerning various issues related to water management. Eutrophication and its inscription on the French political agenda is a very significant case for analysing the difficulty to build such a political community. On the contrary, when there is an opportunity for policy evaluation, which was the case concerning the management of wetlands in France or the implementation of compulsory flows on the French rivers, these communities can emerge. However, the type of integrated expertise and management proposed in these cases of policy evaluations much depends on their methodological choices.